2008
DOI: 10.1038/ncb1712
|View full text |Cite
|
Sign up to set email alerts
|

Monoubiquitinated H2B is associated with the transcribed region of highly expressed genes in human cells

Abstract: Histone modifications have emerged as important regulators of transcription. Histone H2B monoubiquitination has also been implicated in transcription; however, better understanding of the biological significance of this modification in mammalian cells has been hindered by the lack of suitable reagents, particularly antibodies capable of specifically recognizing ubiquitinated H2B (ubH2B). Here, we report the generation of anti-ubH2B monoclonal antibodies using a branched peptide as immunogen. These antibodies p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
364
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 356 publications
(416 citation statements)
references
References 30 publications
50
364
2
Order By: Relevance
“…Another technical breakthrough came with the generation of antibodies that specifically recognize H2Bub [57]. These antibodies enabled the determination of H2Bub genomic distribution by chromatin immunoprecipitation (ChIP), followed by genomic DNA microarray analysis (ChIP/chip) or DNA sequencing (ChIP/Seq).…”
Section: Open Access Under CC By-nc-nd Licensementioning
confidence: 99%
See 2 more Smart Citations
“…Another technical breakthrough came with the generation of antibodies that specifically recognize H2Bub [57]. These antibodies enabled the determination of H2Bub genomic distribution by chromatin immunoprecipitation (ChIP), followed by genomic DNA microarray analysis (ChIP/chip) or DNA sequencing (ChIP/Seq).…”
Section: Open Access Under CC By-nc-nd Licensementioning
confidence: 99%
“…A more feasible strategy to investigate the role of H2Bub in mammalian transcription regulation is to deplete the cells of the responsible E3 ligase, RNF20, via RNAi [61]. Surprisingly, expression microarray analysis of human HeLa cells depleted of RNF20 revealed that, despite the positive correlation between H2Bub and expression levels [57], the expression of most genes was essentially independent on H2Bub levels and was unaffected by RNF20 depletion [57]. Thus, although H2Bub is positively correlated with the transcription process in general, it is not rate-limiting for the transcription of most genes.…”
Section: Monoubiquitylated Histone H2bmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this hypothesis, estrogen-dependent breast cancer cells are able to proliferate without estrogen when RNF40 is knocked down (Prenzel et al, 2011). Surprisingly, the inactivation of RNF20/40 only has a moderate effect on overall gene expression levels (Shema et al, 2008), raising the possibility that the H2Bub1 chromatin mark could be dedicated to the regulation of specific groups of genes rather than the regulation of the whole genome. Indeed, H2Bub1 has been associated with the regulation of inducible genes involved in cell differentiation (Zhu et al, 2005;Fuchs et al, 2012;Karpiuk et al, 2012;Materne et al, 2016) and inflammation (Tarcic et al, 2016), suggesting a role for H2Bub1 in the regulation of inducible rather than constitutive transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic analyses showed that H2Bub1 is enriched in actively transcribed regions of human genes (Minsky et al, 2008) and it has been proposed to be involved in the regulation of global transcriptional elongation (Pavri et al, 2006;Minsky et al, 2008).…”
Section: Introductionmentioning
confidence: 99%